An Examination of the Disparities Between Patient Expectations and Perceptions about Drug Delivery Operations at the Outpatient Pharmacy in the Hospital - Ismeliaoctari; Lana Sari; Ratih Puspita Kusumadewi Purba (RRZ Scientific Publishing, 2023)
Patient satisfaction with services can be determined by comparing patient perceptions and expectations. The Outpatient Pharmacy of Hospital X in Pangkalpinang City experienced problems in drug delivery because the information was not based on medical records and patient clinical data, resulting in biased information being conveyed. It conveyed information can cause differences between patient expectations and perceptions. It analyzed the differences between patient expectations and perceptions of drug delivery activities at the Outpatient Pharmacy of Hospital X Pangkalpinang City based on the 5 SERVQUAL dimensions: reliability, responsiveness, assurance, empathy, and tangibles. This research was a comparative analytic study using a cross-sectional approach. The research instrument was a questionnaire, and it was analyzed using Mann-Whitney. Respondents were patients/families of the Outpatient Pharmacy patients at Hospital X in Pangkalpinang City, totaling 130 people. The results showed significant differences between patient expectations and perceptions of drug delivery activities at the Outpatient Pharmacy at Hospital X Pangkalpinang City, with a P-value <0.05. The most enormous gap between expectations and perceptions was in the empathy dimension. Outpatient Pharmacy officers at Hospital X Pangkalpinang City can improve drug delivery services by focusing on the dimensions of assurance, tangibles, and responsiveness and addressing improvements to empathy and reliability.